Atrioventricular canal defect and genetic syndromes: The unifying role of sonic hedgehog. Issue 2 (23rd May 2018) - Digilio, M.C.; Pugnaloni, F.; De Luca, A.; Calcagni, G.; Baban, A.; Dentici, M.L.; Versacci, P.; Dallapiccola, B.; Tartaglia, M.; Marino, B.
Abstract : The atrioventricular canal defect (AVCD) is a congenital heart defect (CHD) frequently associated with extracardiac anomalies (75%). Previous observations from a personal series of patients with AVCD and "polydactyly syndromes" showed that the distinct morphology and combination of AVCD features in some of these syndromes is reminiscent of the cardiac phenotype found in heterotaxy, a malformation complex previously associated with functional cilia abnormalities and aberrant Hedgehog (Hh) signaling. Hh signaling coordinates multiple aspects of left‐right lateralization and cardiovascular growth. Being active at the venous pole the secondary heart field (SHF) is essential for normal development of dorsal mesenchymal protrusion and AVCD formation and septation. Experimental data show that perturbations of different components of the Hh pathway can lead to developmental errors presenting with partially overlapping manifestations and AVCD as a common denominator. We review the potential role of Hh signaling in the pathogenesis of AVCD in different genetic disorders. AVCD can be viewed as part of a "developmental field, " according to the concept that malformations can be due to defects in signal transduction cascades or pathways, as morphogenetic units which may be altered by Mendelian mutations, aneuploidies, and environmental causes. Abstract :